A new species of the deep-sea genus Bresilia (Crustacea: Decapoda: Bresiliidae) discovered from a shallow-water cave in Madeira - Calado, R.; Chevaldonné, P.; dos Santos, A. (Journal of the Marine Biological Association of the United Kingdom, 2004)
During a recent survey of the biodiversity of shallow-water aphotic marine caves of Madeira Island (north-east Atlantic), 12 specimens of the rare deep-sea shrimp genus Bresilia (Caridea: Bresiliidae) were collected from a depth of 15 m. The collected shrimps are described and illustrated as Bresilia saldanhai sp. nov., increasing to ¢ve known species of the genus. Morphological characters are compared and discussed, and an updated world key for the genus Bresilia is presented. For the ¢rst time, a species of this poorly known genus can be described from a signi¢cant number of intact specimens. This occurrence once more demonstrates the strong environmental similarities and evolutionary ties between marine caves and the deep sea.